The activity of N-acetyl-β-glucosaminidase and its isoenzymes in the renal tissue, serum and urine of patients with renal cancer - Borzym-Kluczyk, Małgorzata; Darewicz, Barbara; Knaś, Małgorzata; Szajda, Sławomir D.; Sulik, Marian; Olszewska, Ewa; Zwierz, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2005)
Renal cancer makes up around 3-4% of human neoplasms. It may metastasise, infiltrate and colonise other tissues. Infiltration and metastasis may depend on changes in the oligosaccharide structures of glycoconjugates of the glycocalyx, basement membranes and extracellular matrix. Oligosaccharides are degraded by endo- and exoglycosidases. N-acetyl-β-glucosaminidase (NAG) produced mainly by the epithelial cells of proximal convoluted renal tubules, is the most active of all exoglycosidases. N-acetyl-β-hexosaminidase is a lysosomal exoglycosidase which hydrolyses β-glycosides of N-acetylglucosamine (GlcNAc) and N-acetylgalactosamine (GalNAc) from glycoconjugates. In human tissues it exists as two major isoenzymes: a thermolabile NAG A and thermostabile NAG B. NAG is a glycoprotein composed of two subunits α and α. Isoenzyme A has composition αβ isoenzyme B ββ, respectively. Genes coding subunit α NAG are localised to chromosome 15, and those coding subunit β are localised to chromosome 5. The cancerous tissue revealed a significantly lower activity, of NAG and its isoenzyme A, and transitional tissue showed an intermediate activity in comparison to control renal tissue. A significant increase in NAG activity was observed in the serum and urine of renal cancer patients, in comparison to control subjects. In conclusion we propose determination of NAG in urine as a potential marker of renal cancer.